Pengaruh Kualitas Pelayanan dan Tingkat Pemahaman Regulasi Terhadap Preferensi Pemilihan Lembaga Keuangan Lokal Melalui Persepsi Nilai di Desa Tamanbali - Karya Mardika Ngakan Made; Daman Sudarman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study was conducted to analyze the influence of service quality and regulatory understanding on selection preference, with perceived value as a mediating variable in local financial institutions in Tamanbali Village. The background of this research is based on the importance of understanding customer behavior in determining their preferred financial institutions amid increasing competition among local financial service providers. This research employs a quantitative approach using the Partial Least Squares (SmartPLS 4) method. Data were collected through questionnaires distributed to respondents who use local financial services in Tamanbali Village, including customers of LPD, BUMDes, and KDMP, with a total sample of 268 respondents. Validity and reliability tests, as well as structural model evaluations, were conducted to assess the strength of the relationships among the research variables. The results indicate that service quality has a positive and significant effect on selection preference, while regulatory understanding has a negative and significant effect on selection preference. Furthermore, perceived value positively and significantly affects selection preference. The mediation test confirms that perceived value significantly mediates the relationship between service quality and regulatory understanding on selection preference. Overall, the findings emphasize that perceived value is a dominant factor shaping customers’ preferences toward village financial institutions. These results are expected to provide theoretical contributions to the development of consumer behavior studies in financial services and practical insights for local financial institution managers in designing strategies to enhance customer value and trust.